The management university in Europe and the procedures for evaluation of the “quality” of teaching and research in Spain - Quirós Fernández, Fernando José (2016)
This article deals with the process of liquidation in which lives the public university in Europe and specifically addresses the case of Spain, establishing an emphasis on the teaching and research evaluation systems of its teaching staff. This group is the one being hardest hit by the systems and techniques of measurement with which the neoliberalism discipline and controls the public universities.